2013
DOI: 10.1007/s00167-013-2809-0
|View full text |Cite
|
Sign up to set email alerts
|

The adductor tubercle as an important landmark to determine the joint line level in total knee arthroplasty: from radiographs to surgical theatre

Abstract: Case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 18 publications
0
31
1
Order By: Relevance
“…[ 14 ] and Iacono et al . [ 15 16 ] concluded that the femoral adductor tubercle was an accurate and stable anatomical landmark for measurement of knee JL position, and that its position was not affected by knee flexion or extension. Weber concluded that internal or external rotation were no influence on measurement result if the angle was <10°.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] and Iacono et al . [ 15 16 ] concluded that the femoral adductor tubercle was an accurate and stable anatomical landmark for measurement of knee JL position, and that its position was not affected by knee flexion or extension. Weber concluded that internal or external rotation were no influence on measurement result if the angle was <10°.…”
Section: Discussionmentioning
confidence: 99%
“…At the femoral side, the change of the joint height of the femur was measured based on a method previously described. 17 The perpendicular distance between the adductor tubercle as the distal point on the medial condylar slope of the femur and the joint line was measured (‘distance D’). The joint line down the femur (JLDF) was defined as the difference between pre- and post-operative distance D.…”
Section: Methodsmentioning
confidence: 99%
“…Femoral rotation and joint line displacement were assessed. Femorotibial joint line height restoration was determined radiographically using the ratio of the adductor tubercle to joint line distance and the femoral width [38].…”
Section: Methodsmentioning
confidence: 99%